A Novel Technique for the Correction of Unilateral Craniofacial Fibrous Dysplasia Using Multiplanar Sequential Cutting Guides. Issue 1 (19th January 2023) - Jain, Rahul; Mahendru, Sanjay; Khazanchi, Rakesh K.
Abstract : In this unique case report, the authors have described a new method for the correction of unilateral craniofacial fibrous dysplasia by using sequential cutting guides. Due to the complex 3-dimensional anatomy of zygoma, it needs to be chiseled in multiple planes to mimic the normal contralateral side. To achieve this, 3 different guides were used one after the other to perform osteotomies in different planes and remove the excess fibrous bone.